Final answer:
To complete the table for the rule y = x - 3, substitute each x into the equation to find y. For example, if x is 7, y is 4 because 7 minus 3 equals 4.
Step-by-step explanation:
The student asked to complete the table for the given rule y = x - 3. To complete the table, you substitute the given x values into the equation and calculate the corresponding y values. The rule states that for any value of x, you subtract 3 to find the corresponding value of y. Therefore, if x is 7, then y is 7 - 3, which equals 4. The complete table would look like this:
- x: 7, y: 4 (because 7 - 3 = 4)
- x: 1, y: -2 (because 1 - 3 = -2)
- x: 7, y: 4 (as before, because 7 - 3 = 4)